1991
DOI: 10.1289/ehp.90-1519493
|View full text |Cite
|
Sign up to set email alerts
|

The potential of exposure biomarkers in epidemiologic studies of reproductive health.

Abstract: To further the development and application of exposure markers in field investigations in reproductive epidemiology, we have synthesized recent examinations of the issues surrounding exposure measurements in reproductive epidemiology. The specific goals of this paper are to define exposure biomarkers and explore their potential uses, particularly as screening tools. The tests for glucaric acid, thioethers, mutagenicity, and porphyrin patterns meet the general criteria for useful exposure screens. For certain x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 95 publications
1
7
0
Order By: Relevance
“…However, we did not find any association between NDELA exposure and urinary DGA. This finding was not entirely unexpected because DGA excretion has been found to increase after exposure to some chemicals, such as pesticides, but not to styrene, dioxin, or toluene (36). In a previous study by our group, no increase was found in steel-plant workers exposed to mineral oils with respect to controls (40).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, we did not find any association between NDELA exposure and urinary DGA. This finding was not entirely unexpected because DGA excretion has been found to increase after exposure to some chemicals, such as pesticides, but not to styrene, dioxin, or toluene (36). In a previous study by our group, no increase was found in steel-plant workers exposed to mineral oils with respect to controls (40).…”
Section: Discussionsupporting
confidence: 71%
“…In a previous study by our group, no increase was found in steel-plant workers exposed to mineral oils with respect to controls (40). A high intraindividual variation in DGA excretion has been described, which may reflect both genetic and environmental factors and may explain these contradictory results (36). We found an association between coffee drinking and DGA urinary values in this study, which suggests that factors other than occupational exposure can influence urinary DGA excretion, and they should therefore be taken into account in occupational and environmental studies.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The characterization of health risk variability for homogeneous and heterogeneous populations is very important information that is needed to develop and evaluate fully the effectiveness and performance of remediation technologies to reduce health risks for the least cost. In this regard, greater use of biological indicators of exposure and disease in epidemiological studies may be an important research activity to continue and to expand (152)(153)(154)(155)(156).…”
Section: Discussionmentioning
confidence: 99%
“…The use of biologic markers in molecular epidemiologic studies of fetal and childhood exposures can circumvent some of these limitations. To date, biologic markers have not been widely used in developmental epidemiology of environmental exposures (16,17); however, they offer the potential to provide quantitative dosimeters of biologic dose and/or indices of biologic effect associated with fetal and childhood exposures to environmental carcinogens and other toxicants. Further, they can facilitate quantification of differences in the magnitude of response in the young relative to that in adults.…”
Section: Introductionmentioning
confidence: 99%